Adaption to increasing slope in diagonal stride: differences between male and female cross-country skiers - Peilegrini, B.; Bortolan, L.; Schena, F. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In a previous work it has been demonstrated how the increasing of the gradient will lead to a significant changes in the parameters that characterize poling action of diagonal stride of roller skiing on a treadmill. The aim of this work is to study if these changes are gender related.